The Impact of Problem-Posing Learning Method on Critical Thinking Skills in terms of Self-Confidence - Hermiyati, Nurul; Yurniwati Yurniwati; Gusti Yarmi (Elementary Teacher Education Program, Majalengka University, 2024)
Elementary school students need help solving math description problems due to weak critical thinking skills. The need for appropriate learning methods for developing critical thinking skills and student self-confidence factors cause the low quality of the mathematics learning process. The purpose of this research is to test the effect of Problem Posing learning method on critical thinking skills in terms of students' self-confidence in mathematics learning. The research methodology applied was an experiment with a 2 x 2 design. The research sample was selected using Cluster Random Sampling with a total sample of 140 students. The research instruments used were the critical thinking skills test in the form of description test questions and the self-confidence questionnaire using the Likert scale. Data analysis began with prerequisite tests in the form of normality and homogeneity followed by two-way ANOVA hypothesis testing and the Tukey test as a further test with the help of SPSS statistical software. The results revealed that the critical thinking skills of students who were given Problem Posing treatment was higher than that of students who were given expository learning treatment; there was an interaction between learning methods and self-confidence in critical thinking skills, critical thinking skills in Problem Posing was higher than expository learning for students who had high self-confidence, and students who had low self-confidence in expository learning had higher critical thinking ability than Problem Posing learning. Based on the results of the study, it can be concluded that the Problem-posing learning method significantly affects critical thinking skills in terms of the self-confidence of elementary school students.